Modeling of co-creation value between end-users and designers towards Malaysian interactive design process / Ramlan Jantan - Jantan, Ramlan (2022)
Nowadays, co-creation method has become a new development trend in the era of technology. Towards this scenario, most of design businesses is currently transformed their development strategy from a good-dominant into service- dominant where more attention is given to the end-users and their roles in the development process. As a result, the conventional development process is been replaced with more cooperative approach. Towards co-creation trail therefore, numerous studies have been conducted to explore the extension of co-creation method in the design development process. Most of the results concluded, the understanding of this concept is still shallow and many design companies are lack of understanding on creating users value particularly on user participation in design development process. Furthermore, in Malaysia so far there is no certain process or models exist in order to show how co-creation method is really can be shaped in context of Malaysian interactive design application. Thus, this research have explored how Malaysian design companies understand and experienced the proficiency of co-creation method in their design process. Hence, resulted of experiences accumulated from both parties involved: the users and designers. This study have been conducted using mixed methods research approach which are qualitative exploratory with contextual analysis, in-depth interview, focus group simulation and observation. Results of data collection and specifically primary data indicated co-creation value is important to be an agent of change to Malaysia design industry. Significantly, co-creation value is applicable for interactive multimedia industry in Malaysia pertinent to NPD (new product development), reliable and core of new economics booster. Co-creation approach are effective application transcend interactive multimedia to new era of multiplicity creation value beneficial for practitioner and academia in Malaysia. A propose conceptual model as a blueprint for multimedia industry to apply co-creation value to their production process have been developed and expectedly beneficial for development of new product and new value proposition. Furthermore, the model would be a guiding for future researcher to further develop the concept and utilize it for industry practice.